Effects of Increased Peritoneal Clearances on Mortality Rates in Peritoneal Dialysis - Ramón Paniagua; Dante Amato; Edward F. Vonesh; Ricardo Correa‐Rotter; Alfonso Ramos; John Moran; Salim Mujais (2002)
ABSTRACT. Small-solute clearance targets for peritoneal dialysis (PD) have been based on the tacit assumption that peritoneal and renal clearances are equivalent and therefore additive. Although several studies have established that patient survival is directly correlated with renal clearances, there have been no randomized, controlled, interventional trials examining the effects of increases in peritoneal small-solute clearances on patient survival. A prospective, randomized, controlled, clinical trial was performed to study the effects of increased peritoneal small-solute clearances on clinical outcomes among patients with end-stage renal disease who were being treated with PD. A total of 965 subjects were randomly assigned to the intervention or control group (in a 1:1 ratio). Subjects in the control group continued to receive their preexisting PD prescriptions, which consisted of four daily exchanges with 2 L of standard PD solution. The subjects in the intervention group were treated with a modified prescription, to achieve a peritoneal creatinine clearance (pCrCl) of 60 L/wk per 1.73 m 2 . The primary endpoint was death. The minimal follow-up period was 2 yr. The study groups were similar with respect to demographic characteristics, causes of renal disease, prevalence of coexisting conditions, residual renal function, peritoneal clearances before intervention, hematocrit values, and multiple indicators of nutritional status. In the control group, peritoneal creatinine clearance (pCrCl) and peritoneal urea clearance (Kt/V) values remained constant for the duration of the study. In the intervention group, pCrCl and peritoneal Kt/V values predictably increased and remained separated from the values for the control group for the entire duration of the study ( P < 0.01). Patient survival was similar for the control and intervention groups in an intent-to-treat analysis, with a relative risk of death (intervention/control) of 1.00 [95% confidence interval (CI), 0.80 to 1.24]. Overall, the control group exhibited a 1-yr survival of 85.5% (CI, 82.2 to 88.7%) and a 2-yr survival of 68.3% (CI, 64.2 to 72.9%). Similarly, the intervention group exhibited a 1-yr survival of 83.9% (CI, 80.6 to 87.2%) and a 2-yr survival of 69.3% (CI, 65.1 to 73.6%). An as-treated analysis revealed similar results (overall relative risk = 0.93; CI, 0.71 to 1.22; P = 0.6121). Mortality rates for the two groups remained similar even after adjustment for factors known to be associated with survival for patients undergoing PD ( e.g. , age, diabetes mellitus, serum albumin levels, normalized protein equivalent of total nitrogen appearance, and anuria). This study provides evidence that increases in peritoneal small-solute clearances within the range studied have a neutral effect on patient survival, even when the groups are stratified according to a variety of factors (age, diabetes mellitus, serum albumin levels, normalized protein equivalent of total nitrogen appearance, and anuria) known to affect survival. No clear survival advantage was obtained with increases in peritoneal small-solute clearances within the range achieved in this study.